Pola Hubungan Patron-Klien Peternak Ayam Potong Broiler di Desa Puasana Kecamatan Amonggedo Kabupaten Konawe - Sukratman, I Made; Saptiani, Komang Juni (Universitas Batanghari Jambi, 2022)
This study aims to determine the pettern of the patron-client relationship of broiler breeders in Puasana Village, amonggedo District, Konawe Regency and the income of broiler breeders based on the pattern of patron-client relationship in Puasana Village, amonggedo District, Konawe Regency. This research was carried out in the village of fasting, amonggedo district, konawe, the population in this study were 10 clients and 3 patrons, data consists of primary data and secondary data, analyzed qualitatively. The reluts showed that the pattern of patron-client relationship among broiler chicken breeders in the fasting village, amonggedo sub-district, konawe district is an economic relationship that can affect the level of income or the economy of the community,especially in broiler farming or other businesses because economic relations are needed in running a business relationship reciprocity which is a reciprocal exchange between individuals or between groups that mutually benefit each other and accept even though it is not balanced and each party, the ridge of loyalty which is an act of retribution or giving between the client for what has been received so far from the patron, so that patron can feel satisfaction from the client personal relationship which is an international kornitinen relationship between individuals that cannot be replaced and which is influenced by a rule the average income of a farmer in one production cycle is Rp.47.774.966,-.